Implementasi Perbandingan Asas Equality Before The Law Dalam Sistem Peradilan Pidana Di Indonesia Dengan Negara Lain - Amri, Ahmad Ihsan; Anggono, Bayu Dwi (Al-Syakhsiyyah: Journal of Law and Family Studies, 2024)
Equality before the law is one of the most important and powerful principles in Indonesia's system of law enforcement. As a law-abiding state, certainly the application of this principle illustrates that every citizen has the same degree or position in the law without exception. The law presented no distinction for any party, it was expressly explained in chapter 27 of the verse (2) the 1945 law. The study aims to see if there is a link between the principle of equality before the law and Indonesia's criminal justice system and how it applies. In writing the study using the normative type of legal study method using the research approach: a legal approach, a conceptual approach and compartive approach. From this study, the conclusion is that the implemntation of equality before the law must be interpreted dynamically, not statically, both in Indonesia and other countries. This means that Indonesia, Jerman and Belanda view that equality before the law must be harmonized with the same treatment for everyone. Justice carried out by the state must provide benefits to all people, and the ask of law is to maintain justice so that it can reach all people without exception. Everyone has the same acces to justice regardless of whether they are rich or poor.